Genetolingvistična klasifikacija vzhodnoslovanskih jezikov - Šekli, Matej (Slavia Centralis, 2020)
Genetic classification of East Slavic Languages
Keywords: genetic linguistics; geolinguistics; geolect; genetic classification; comparative linguistics; East Slavic languages